SPATIAL LOCATIONS OF FACING AND ORNAMENTAL STONES DEPOSITS AND OUTCROPS IN EAST KAZAKHSTAN - Chernenko, Z.; Mizernaya, M.; Teut, E. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
The topicality of carrying out the study gives rise to a need to assess already prospected deposits and locate new deposits and outcrops of facing and ornamental stones in East Kazakhstan. The paper is dedicated to the analysis of these deposits and outcrops locations on the basis of structural and formation comparison taking into account the peculiarities of the folds development, magmatism, metamorphism and deep-seated faults. The authors give a short description of potentially productive zones (Beloubinsk-South Altai, Rudny Altai, Irtysh area, Kalbin area) and 28 potentially productive resource patches (gabbroids, granitoids, marble and marble limestone, quartzites, volcanogenic rocks) and provide with results of the analytical studies of the rocks. The article describes conclusions about association of facing and ornamental stones deposits and outcrops with curved complex fold zones. Spatial locations of the deposits and outcrops have linear structural features when compared to the major structural elements of fold-arcs, fore deeps and marginal faults of the Kazakhstan fold belts. Groups of facing and ornamental stones are associated with different epochs of consolidation. The complex of studies, including exploratory geological surveys, metallogenic studies, is recommended to conduct.
Keywords: facing and ornamental stones; potentially productive zones; innovative technology; East Kazakhstan